2018
DOI: 10.1089/fpd.2017.2408
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Enterotoxin Genes inStaphylococcus aureusIsolates from Pork Production

Abstract: In this study, 130 Staphylococcus aureus isolates from samples associated with pork production were tested for prevalence of 18 staphylococcal enterotoxin (SE) genes. Approximately 94.6% (123/130) of isolates from different stages of pork production harbored one or more SE genes forming 37 different enterotoxin gene profiles. Seb was present in 60.0% of the S. aureus isolates, the highest among the genes tested. The genes, sed, sej, seo, sep, ser, and seu, were not found. The five classical SE genes (including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 36 publications
2
10
0
Order By: Relevance
“…The most prevalent toxin genes were the egc encoded genes seg , sei , sem , sen , seo and seu , which were detected in 11 strains belonging to CC1, CC7, CC9, CC49, and CC398. On conventional cuts of pork meat similar enterotoxin profiles have been reported [10,45]. Interestingly, only one strain isolated from a heart harbored the sec and sel genes.…”
Section: Resultssupporting
confidence: 67%
“…The most prevalent toxin genes were the egc encoded genes seg , sei , sem , sen , seo and seu , which were detected in 11 strains belonging to CC1, CC7, CC9, CC49, and CC398. On conventional cuts of pork meat similar enterotoxin profiles have been reported [10,45]. Interestingly, only one strain isolated from a heart harbored the sec and sel genes.…”
Section: Resultssupporting
confidence: 67%
“…According to our phenotypic tests, a S. aureus isolate, which also harboured the seb gene, was positive for enterotoxin B production (Table 4). In parallel to the present study, the prevalence of se genes of S. aureus isolates from pork were also high at rates of 94Á6 and 75% in China (Zhang et al 2018) and Poland (Bystron et al 2018) respectively. According to our phenotypic tests, a S. aureus isolate, which also harboured the seb gene, was positive for enterotoxin B production (Table 4).…”
Section: Prevalence Of Se and Tst Genessupporting
confidence: 78%
“…In this study, 68 out of 385 raw goat milk samples (17.6%, 68/385) were positive with S. aureus . The prevalence of S. aureus is significantly lower than that in the previous report that showed the contamination rate of S. aureus in pork industry was 26% (130/501) in China [28]. Similarly, it was also obviously less than that in other reports which demonstrated that S. aureus was detected in 53.5% (153/286) of the bulk tank milk samples in Italy [29], and 46% (47/104) of the bulk tank milk samples in the United States [30].…”
Section: Discussionmentioning
confidence: 65%